Analisis Intertekstual Kristeva; antara Metode Ilmiah Rudolf Carnap dan Pemahaman Hadis Muhammad Syuhudi Ismail - Almuttaqin, Muhammad; Irwansya, Irwansya (Journal of Islamic Thought and Philosophy, 2023)
This study explores the differences in approach between the scientific method and critical discussion of hadith in the thought of Rudolf Carnap and Muhammad Shuhudi Ismail. Carnap emphasized empirical verification, while Shuhudi Ismail highlighted the historical and cultural context in the understanding of hadith. The research aims to analyze the implications and integration of these two approaches in hadith analysis, as well as identify their potential integration in the perspective of Julia Kristeva. This study uses text analysis to compare Carnap and Syuhudi Ismail's perspectives on the scientific method and critical discussion of hadith. The integration of this approach is analyzed through Kristeva's intertextual approach. The results showed a difference between Carnap's approach that focused on empirical verification and rigorous logic and Syuhudi Ismail's contextual approach that emphasized understanding hadith in historical and cultural contexts. The integration of these two perspectives through Kristeva's intertextual analysis allows for a deeper and scientifically strong understanding of understanding in hadith studies.